2019
DOI: 10.1016/j.schres.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E-ε4 allele predicts escalation of psychotic symptoms in late adulthood

Abstract: Background: Research on a putative link between apolipoprotein-ε4 allele (APOE-ε4) and schizophrenia has been inconclusive. However, prior studies have not investigated the association between APOE-ε4 and symptom trajectories, nor has the existing literature taken into account the potentially moderating effect of age in genetic association studies. Methods: The association between APOE-ε4 and four symptom dimensions was investigated in a longitudinal study of 116 individuals with schizophrenia initially assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Recent meta-analyses and longitudinal analyses have suggested APOE-ε4 as an age-related risk factor for aggressive hallucinations and delusions, and as having an age-mediated pathophysiological role in schizophrenia. This finding could support those individuals with the APOE-ε4 allele being treated with more intensive monitoring and additional interventions in mid-to-late life [ 65 ]. However, these results need to be replicated in other clinical studies.…”
Section: Precision Medicine In Late-onset Psychosismentioning
confidence: 79%
“…Recent meta-analyses and longitudinal analyses have suggested APOE-ε4 as an age-related risk factor for aggressive hallucinations and delusions, and as having an age-mediated pathophysiological role in schizophrenia. This finding could support those individuals with the APOE-ε4 allele being treated with more intensive monitoring and additional interventions in mid-to-late life [ 65 ]. However, these results need to be replicated in other clinical studies.…”
Section: Precision Medicine In Late-onset Psychosismentioning
confidence: 79%
“…By comparing the above studies, we speculate that these different results between our current study and other studies may be partly due to differences in population, sample composition, type of schizophrenia, and synergy/interaction effects with other variants. Also, the age of patients could be a potential reason, and a meta-analysis indicated that ApoE -ε4 may play an age-mediated pathophysiological role in schizophrenia [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this is that the combined effect of rs429358 and rs7412, but not rs429358 alone, has a significant effect on the PANSS score of patients with schizophrenia. Furthermore, a longitudinal study found that ApoE -ε4 predicted worsening severity of hallucinations and delusions in patients with schizophrenia in late adulthood [ 63 ]. Hence, it is worth to perform a follow-up study between ApoE rs429358 and subsequent PANSS scores.…”
Section: Discussionmentioning
confidence: 99%
“…APOE ε3 is the most frequent allele, whereas the ε4 allele is the most common genetic risk factor for AD, leading to an earlier onset of the disease as well [ 88 ]. Furthermore, APOE ε4 has been linked to hallucinations and delusions in AD patients [ 89 ], and may be also an age-related risk factor for the worsening of delusions and hallucinations in patients with schizophrenia [ 90 ]. In PD, the APOE ε4 allele has been also associated with earlier disease onset [ 91 , 92 ] and a greater risk of dementia [ 93 ], although there is also evidence that does not confirm these relationships [ 92 , 94 ].…”
Section: Genetic Architecture Of Psychosis In Parkinson’s Diseasementioning
confidence: 99%